2018
DOI: 10.1159/000489652
|View full text |Cite
|
Sign up to set email alerts
|

FG-4592 Accelerates Cutaneous Wound Healing by Epidermal Stem Cell Activation via HIF-1α Stabilization

Abstract: Background/Aims: Regional hypoxia promptly develops after trauma because of microvascular injury and increased oxygen consumption. This acute hypoxia plays a positive role in early skin wound healing. One of the mechanisms underlying the beneficial effects of acute hypoxia on wound healing may be increased hypoxia-inducible factor-1 (HIF-1α) expression. HIF-1α may affect the wound-healing process through many aspects, including angiogenesis, metabolism, and extra-cellular matrix synthesis and remodelling. Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Second, because it is already under phase 3 clinical trials, the potential of roxadustat for the treatment of diabetic wounds in humans could be investigated relatively quickly. Third, in addition to its proangiogenetic effect, as indicated in the present study, roxadustat was reported to improve epidermal stem cell proliferation and motility, which could accelerate the re‐epithelialization of keratinocytes to promote cutaneous wound healing. Thus, roxadustat may be a promising candidate for clinical trials for the treatment of diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 53%
“…Second, because it is already under phase 3 clinical trials, the potential of roxadustat for the treatment of diabetic wounds in humans could be investigated relatively quickly. Third, in addition to its proangiogenetic effect, as indicated in the present study, roxadustat was reported to improve epidermal stem cell proliferation and motility, which could accelerate the re‐epithelialization of keratinocytes to promote cutaneous wound healing. Thus, roxadustat may be a promising candidate for clinical trials for the treatment of diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 53%
“…And Ruthenborg et al first systematically discussed the potential for the use of PHD inhibitors to treat tissue injuries and wounds [17]. Numerous studies demonstrated that PHD-targeted treatment, such as using DMOG or designed compounds, e.g., FG-4592, had satisfactory outcomes in wound healing via the HIF-1 signalling pathway [8, 1822]. However, the upregulated HIF-1 via VHL inhibition remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is not limited to either macrophages or muscle cells but might involve all cells with reduced Phd2 activity. In view of the upcoming production of pharmacologic PHD inhibitors, application of PHD inhibitors may turn out to be advantageous after skeletal muscle trauma to accelerate regeneration [64,65].…”
Section: Plos Onementioning
confidence: 99%